1959
DOI: 10.1111/j.1399-3054.1959.tb07973.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Microsomal Ribonucleoproteins in the Time Course of the Germination Stage as Revealed by Electrophoresis

Abstract: It has been reported that at the .outset of germination of Vigna sesquipedalis seeds the decrease in ribonucleic acid (RNA) content in a pair of cotyledons is precisely balanced with the increase in RNA in the seedling axis (plumules+ epi-and hypocotyls +radicle), whereas in the isolated cotyledons from the growing tissues no change in the RNA level takes place (Oota and Osawa, 1). On the other hand, in the hypocotyl at the middle of the germination stage (the definition of the germination stage has been given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1961
1961
1978
1978

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…This is especially stuggeste(d in the case of ntucleic acid (figs 10,14). WVhether the ntucleic acids move as macromolecules (13,17,18) or are first degraded and resynthesized in the embryonic axis (4, 7,1 1, 14) is impossible to ascertain from this typo of data. Information on 3P or nucleotide incorporation into nucleotides and nucleic acids are needed to clarify this point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially stuggeste(d in the case of ntucleic acid (figs 10,14). WVhether the ntucleic acids move as macromolecules (13,17,18) or are first degraded and resynthesized in the embryonic axis (4, 7,1 1, 14) is impossible to ascertain from this typo of data. Information on 3P or nucleotide incorporation into nucleotides and nucleic acids are needed to clarify this point.…”
Section: Discussionmentioning
confidence: 99%
“…This stems primarily from the uncertainty of the natture of the mobilization, transfer and tutilization of other reserve phosphate containing compouinds. For example, some investigators believe that ntucleic acids are transported from reserve tissule to axis intact or as the nticleotides (13,17,18) while others feel that some de novo synthesis of nucleic acids does occur in the axis (4,7,11). Similarly, it is not c!ear whether phospholipids move from the reserve tissue to the axis or whether they are synthesized de novo in the axis, althotugh the latter appeared to be the case for cotton germination (5).…”
mentioning
confidence: 99%
“…Oota et al (26,27) have found that the cotyledons of bean seeds contain large amounts of RNA which accumulated during maturation of the seeds, and with the start of the germination the level of this RNA (termed storage RNA) is reduced sharply, and the drop is balanced with an increase in the growing seedling axis. According to them, the RNA reserved in bean cotyledons is broken down into small size free RNA (termed transport RNA), and this free RNA is further transported to actively growing portions or RNA sinks to be reutilized there for the reconstruction of ribosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Oota and Takota (12) have proposed that there ar-e at least two types of RNA-s i.e. functional and transportable, in bean germ tissues.…”
mentioning
confidence: 99%
“…Oota et al (11,12) have examined nucleic acid metabolism in germinating see(ls, and have found large amounts of RNA stored in the cotyledons of a bean. Germination resulted in a steady decrease in the RNA content of the cotyledlons with an increased RNA content in the seedling.…”
mentioning
confidence: 99%